The Influence of Reporting Systems, Clarity of Budget Targets and Accounting Control on Performance Accountability of Government Agencies (Study on Regional Apparatus Organizations in Sigi Regency, Central Sulawesi) - MILE, Yuldi; NATSIR, Muhammad; TENRIPADA, Tenripada; SRIWINARTI, Lis (PT Keberlanjutan Strategis Indonesia, 2023)
This study aims to examine and analyze the effect of reporting systems, clarity of budget targets and accounting controls on performance accountability of government agencies. This type of research is survey research with quantitative research methods and uses primary data and secondary data. The population in this study is the Regional Apparatus Organization (OPD) in Sigi Regency, Central Sulawesi Province. The sampling technique was purposive sampling, with 2 respondents in each OPD, namely 60 respondents. The analysis technique used is the classical assumption test, multiple linear regression analysis, residual test and hypothesis testing used, namely the simultaneous test (f test) and partial test (t test). The results of this study indicate that the Reporting System, Clarity of Budgetary Targets and Accounting Control simultaneously have a significant effect on Government Agencies' Performance Accountability, Reporting Systems have no significant effect on Government Agencies' Performance Accountability, Clarity of Budgetary Targets has a significant effect on Government Agencies' Performance Accountability and Accounting Control has a significant effect on Performance Accountability of Government Agencies.